2017
DOI: 10.3390/v9090244
|View full text |Cite
|
Sign up to set email alerts
|

Key Determinants of Human α-Defensin 5 and 6 for Enhancement of HIV Infectivity

Abstract: Defensins are antimicrobial peptides important for mucosal innate immunity. They exhibit a broad spectrum of activity against bacteria, viruses, and fungi. Levels of α-defensins are elevated at the genital mucosa of individuals with sexually transmitted infections (STIs). Somewhat paradoxically, human α-defensin 5 and 6 (HD5 and HD6) promote human immunodeficiency virus (HIV) infectivity, and contribute to STI-mediated enhancement of HIV infection in vitro. Specific amino acid residues of HD5 and HD6 that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…HNP1-and HD5-promoted viral infection has also been observed with certain serotypes of HAdV as reported by 41), ( 5) inhibition of nuclear import of viral RNA (30,39), and ( 6) suppression of HIV transcription (30,39,167). Infection-promoting mechanisms include: (7) enhancing viral adhesion/attachment (25,56,57,59), and (8, 9) disrupting tight junction to promote trans-epithelial transmission of HIV (60).…”
Section: Defensins In Viral Infectionmentioning
confidence: 66%
See 4 more Smart Citations
“…HNP1-and HD5-promoted viral infection has also been observed with certain serotypes of HAdV as reported by 41), ( 5) inhibition of nuclear import of viral RNA (30,39), and ( 6) suppression of HIV transcription (30,39,167). Infection-promoting mechanisms include: (7) enhancing viral adhesion/attachment (25,56,57,59), and (8, 9) disrupting tight junction to promote trans-epithelial transmission of HIV (60).…”
Section: Defensins In Viral Infectionmentioning
confidence: 66%
“…More recent studies, mostly by the same research groups who demonstrated the beneficial role of defensins in controlling viral infection, unveil infection-promoting effects of defensins in HIV-1 and certain serotypes of HAdV infections (25,51,(56)(57)(58)(59)(60). Chang and colleagues reported that HD5 and HD6, induced by Neisseria gonorrhoeae infection in a cervicovaginal tissue culture system, increase HIV infectivity in a CD4-and HIV coreceptor-independent manner (25).…”
Section: Defensins In Viral Infectionmentioning
confidence: 99%
See 3 more Smart Citations